Autoscopia e desenho: a mediação em uma sala de educação infantil - Tosta, Cintia Gomide (2006)
Although the study of early handwriting in children arouse the interest of professionals from Psychology, Education and Art, it is noticed that the pedagogic practice of many teachers from children s education, related to draws of their students is still sustained in the conception of drawing as a hobby, out of any area of development, not only the visual-motor, not contextualized according to the social-cultural circle and pedagogic interaction and mediation. The current study, based on the historical-cultural theory, had as subject taking part on the research a teacher from Children s Education from a public school of Uberaba (MG), used a qualitative methodology and had as objectives to investigate if the utilization of autoscopy procedures could give conditions to the teacher of rethinking and reorganize her concepts and pedagogic actions referring to the children s draw. Firstly, her classes have been recorded by video in which children of five years old realized activities with drawing. Following this, the tapes were transcript and afterward the researcher realized sessions of autoscopy with the teacher. This procedure consisted in video recording of the subject in her daily pedagogic practice, with sessions after filming, in order to make commentaries about the images. In this research, during the autoscopy there was the researcher s mediation, which presented questions and observation in order to deepen the dialogue between the teacher and the recorded images, whose content consisted in the action with the students in their drawing activities. During the working, the autoscopy procedure revealed an interesting possibility of auto-evaluation of the practice of the teacher, by means of the analysis of the filmed images, of questioning the senses of images and the dialogues between the teacher and the researcher, which suggested in these anxieties about the early handwriting in children, reflecting about her educative practice and reorganization of her pedagogic activities.